Neonatal brucellosis: A case report - Abdul Rahman M. Alnemri; Adnan Hadid; Shaik Asfaq Hussain; Ali M. Somily; Badr H. Sobaih; Abdulkarim Alrabiaah; Awad Alanazi; Zahid Shakoor; Sarah AlSubaie; Naema Meriki; Abdelmageed M. Kambal (Journal of Infection in Developing Countries)
Although brucellosis is not uncommon in Saudi Arabia, neonatal brucellosis has been infrequently reported. In this case of neonatal brucellosis, Brucella abortus was isolated by blood culture from both the mother and the neonate. Serology was positive only in the mother.